2014
DOI: 10.1186/1297-9686-46-44
|View full text |Cite
|
Sign up to set email alerts
|

The 80-kb DNA duplication on BTA1 is the only remaining candidate mutation for the polled phenotype of Friesian origin

Abstract: BackgroundThe absence of horns, called polled phenotype, is the favored trait in modern cattle husbandry. To date, polled cattle are obtained primarily by dehorning calves. Dehorning is a practice that raises animal welfare issues, which can be addressed by selecting for genetically hornless cattle. In the past 20 years, there have been many studies worldwide to identify unique genetic markers in complete association with the polled trait in cattle and recently, two different alleles at the POLLED locus, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 13 publications
2
42
0
Order By: Relevance
“…First identified in Holstein‐Friesian cattle, the Friesian POLLED variant is approximately 200 kb downstream of the Celtic variant and is an 80 128 bp duplication of the sequence between 1 909 352 and 1 989 480 bp (Fig. ) (Medugorac et al ; Allais‐Bonnet et al ; Rothammer et al ). The duplicated segment is located immediately after the original sequence and is in the same orientation.…”
Section: Polled Genetic Variantsmentioning
confidence: 99%
See 2 more Smart Citations
“…First identified in Holstein‐Friesian cattle, the Friesian POLLED variant is approximately 200 kb downstream of the Celtic variant and is an 80 128 bp duplication of the sequence between 1 909 352 and 1 989 480 bp (Fig. ) (Medugorac et al ; Allais‐Bonnet et al ; Rothammer et al ). The duplicated segment is located immediately after the original sequence and is in the same orientation.…”
Section: Polled Genetic Variantsmentioning
confidence: 99%
“…Further research confirmed that this variant segregated in polled Holsteins that did not carry the Celtic POLLED allele (Wiedemar et al ). As with the Celtic POLLED variant, the Friesian POLLED variant does not disrupt any known coding sequence, splice site or intronic region, or any known regulatory regions (Rothammer et al ).…”
Section: Polled Genetic Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this simulation, a single locus was assumed to control polledness, but in reality the polled locus is more complex than HH3 and has at least two mutations on BTA1 that result in hornless cattle [36,37]. All gene-editing methods resulted in significant rates of allele frequency change (Table 4), with rates of change increasing with the efficiency of the technology (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Polledness in cattle is an autosomal dominant trait; however, all heterozygotes had horns in this study. Although the polledness allele was repeatedly mapped to BTA1 in several cattle breeds (Georges et al, 1993;Harlizius, Tammen, Eichler, Eggen, & Hetzel, 1997;Medugorac et al, 2012;Nicholas, 2015;Rothammer et al, 2014;Schmutz, Marquess, Berryere, & Moker, 1995), the causative allele of the functional gene in the region remains unknown (Nicholas, 2015); thus future studies on the risk allele are required to determine whether the SNP was associated with polledness in Japanese Black cattle. The genomic position contained in both position-unassigned and assigned SNP respectively.…”
Section: Ifngr2 (G1390292g>a) In Bta1 Was Found In 14 Individualsmentioning
confidence: 99%